Contributions of sustainable practices for the consolidation of sustainable tourism in Brazil - Garlet, Valéria; Grellmann, Camila Pascotini; Madruga, Lucia Rejane da Rosa Gama (Revista de Administração da UFSM, 2021)
Purpose – This research aims to analyze sustainable practices of 421 tourists, through a quantitative study (survey method). Design/methodology/approach – The questionnaire identified the choices and attitudes related to transportation, lodging, environmental impact, social responsibility, tours, airfare purchase, shopping, food, local culture and nature. Findings – The results showed that most respondents say they practice sustainability when traveling as tourists and try to assist other tourists by teaching and transmitting the principles of minimum impact whenever there is an opportunity. However, some research results are worrisome: only 19.72% of the respondents plan their trips thinking about the environmental impact and only 17.58% verify if the lodging environment adopts sustainability practices. In addition, 46.56% were indifferent about buying in stores and restaurants with sustainable practices. Originality/value (mandatory) – Thus, there is still much to evolve regarding better choices and attitudes. With the development of sustainable practices, it will be possible to achieve favorable tourism for all.